Hemophagocytic Lymphohistiocytosis in the adult critically ill: a narrative review of case reports and case series - Montrucchio, Giorgia; Traversi, Riccardo; Arrigo, Gabriele; Bonetto, Chiara; Sales, Gabriele; Busca, Alessandro; Fanelli, Vito; Filippini, Claudia; Brazzi, Luca (Frontiers in Medicine, 2025)
BackgroundHemophagocytic Lymphohistiocytosis (HLH) is a rare life-threatening syndrome characterized by hyperinflammation caused by abnormally activated macrophages and cytotoxic T cells overlapping with sepsis and multi-organ disfunction (MOD). Its frequency is probably underestimated.MethodsPatients’ data were extracted from a literature search performed on PubMed (MEDLINE) and EMBASE using the following search terms: “Hemophagocyitic Lymphohistiocytosis” OR “HLH” OR “MACROPHAGE ACTIVATING SYNDROME” OR “MAS” AND “Intensive Care Unit” OR “Critical Care” OR “ICU.” Search was limited to articles published after 2014, when HScore was proposed.ResultsWe found 126 case reports and case series for a total of 148 patients with an overall mortality of 47.5%. Main triggers were infections (111 patients; 88.1%) followed by dysimmune disorders (29 patients; 19.7%) and hematological malignancies (20 patients; 13.6%). The following factors were associated with increased ICU mortality: viral infection (76 patients; 52.8%) p = 0.0071 and p = 0.0086 at multivariate analysis for SARS-CoV-2, hematological malignancies (p = 0.0035 at univariate analysis; p = 0.0083 at multivariate analysis), invasive mechanical ventilation (116 patients; 83.3%) p = 0.0060 at univariate analysis not confirmed in multivariate analysis (p = 0.0599). Corticosteroids were associated with reduced ICU mortality at univariate analysis (86 patients; 59.7% p = 0.0250) not confirmed at multivariate analysis (p = 0.7196).ConclusionEvidence from our analysis confirms the severity and rapid evolution of HLH, suggesting the importance of prompt clinical suspicion. Since HLH can be found in different hospital settings, including ICU, we believe that this syndrome should be considered in differential diagnosis for all patients presenting with MOD with unclear etiology. Development of specific diagnostic and therapeutic schemes should be considered a priority.